2017
DOI: 10.1111/jocn.13696
|View full text |Cite
|
Sign up to set email alerts
|

Peanut allergy as a family project: social relations and transitions in adolescence

Abstract: In the management of peanut allergy in adolescence, it is important to consider not only the smaller biological family unit (mothers, fathers and siblings) but to also take a wider perspective to include others such as stepfamily and friends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 33 publications
1
50
0
2
Order By: Relevance
“…93 For those at risk of anaphylaxis, maintaining the balance between taking the risk seriously and not allowing the risk to dominate their lives was reported to be difficult. 83,84,94,95 Thus, risk-taking behaviours were less common in adolescents with an established education plan for their food allergy. 96…”
Section: Knowledge and Beliefsmentioning
confidence: 99%
See 3 more Smart Citations
“…93 For those at risk of anaphylaxis, maintaining the balance between taking the risk seriously and not allowing the risk to dominate their lives was reported to be difficult. 83,84,94,95 Thus, risk-taking behaviours were less common in adolescents with an established education plan for their food allergy. 96…”
Section: Knowledge and Beliefsmentioning
confidence: 99%
“…Asthma, allergy and the risk of anaphylaxis have been shown to affect not only the young person but also all family members 84,94,95,102,103 ( Table 7). However, adolescents often do not report asthma symptoms to caregivers.…”
Section: Familiesmentioning
confidence: 99%
See 2 more Smart Citations
“…One study in peanut allergy found that a subset of parents of a child with peanut allergy experienced high levels of parenting stress [ 19 ]. Parents of a child with peanut allergy have also expressed difficulties with their child’s transition to independence and their own subsequent loss of control [ 20 ], suggesting that the child’s age may influence HRQL burden for caregivers. As discussed previously, one study found that caregiver gender may also influence caregiver burden in peanut allergy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%